"American = English Speaker" Before "American = White": The Development of Children's Reasoning About Nationality. Issue 5 (24th May 2017) - DeJesus, Jasmine M.; Hwang, Hyesung G.; Dautel, Jocelyn B.; Kinzler, Katherine D.
Abstract : Adults implicitly judge people from certain social backgrounds as more "American" than others. This study tests the development of children's reasoning about nationality and social categories. Children across cultures (White and Korean American children in the United States, Korean children in South Korea) judged the nationality of individuals varying in race and language. Across cultures, 5‐ to 6‐year‐old children ( N  =   100) categorized English speakers as "American" and Korean speakers as "Korean" regardless of race, suggesting that young children prioritize language over race when thinking about nationality. Nine‐ and 10‐year‐olds ( N  =   181) attended to language and race and their nationality judgments varied across cultures. These results suggest that associations between nationality and social category membership emerge early in life and are shaped by cultural context.